Prof. Vera Gancheva competition for translation from Scandinavian languages (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
In early 2025, the Scandinavian Studies program at the Department of German and Scandinavian Studies at Sofia University St. Kliment Ohridski held the fourth edition of the competition for the translation of fiction and poetry for students and pupils studying Scandinavian languages. The competition is dedicated to the memory of Prof. Dr. Vera Gancheva, a prominent Scandinavist, translator, teacher, publisher, and scholar. A record number of participants (40) took part in the fourth edition of the competition, with a total of 67 translations.